PHYTOCHEMICAL ANALYSIS, NUTRITIONAL VALUE AND ETHNOBOTANICAL KNOWLEDGE OF Pelargonium quercetorum AGNEW (Geraniaceae) - MAHDI, HONAR SAFAR (Journal of Duhok University, 2020)
Pelargonium quercetorum Agnew is an edible wild species of Pelargonium genus which has a lot of concern in term of ethnobotanical knowledge, nutrition value and phytochemical analysis. Traditionally, it was providing local and rural people medicines and food security. Nowadays, wild edible plants (WEPs) become a central action to preserve the culture that belongs to the natural heritage. Thus, the aim of this research is to investigate ethnobotanical knowledge related to the traditions, phytochemical and nutritional value of P. quercetorum. Semi questionnaire has been used in Deralok town for ethnobotanical knowledge determination. The findings showed the main threats were overgrazing and overharvesting of this WEPs; a quantity of (10kg) took per year as a food and medicines during spring season. The plant was in a high abundance but required bio-conservation alongside it can be taken together with medication with the very rare side effect on the people. Furthermore, the analysis part has been done in the laboratories of college of agricultural engineering science, University of Duhok, Kurdistan region of Iraq. The findings of this research shown interestingly the highest level contents of (fat=3.68g / 100g, carbohydrate=46.78g /100g, dry matter moisture content=10.93g / 100g and fibers=20.56g / 100g), macro mineral (Ca=4512.9mg / 100g and Mg=229.69mg / 100 g), micro minerals (Zn=4.398mg / 100 g, Mn=3.926mg / 100 g and Cu=1.074mg / 100g) were seen in leaves part. But, the highest content of (Energy value 185.44g/100g, Protein 23.38g/100g and Ash 7.63g / 100g), macro mineral (P=928.5mg / 100g, S=4.036mg / 100g, K=1147.9mg/100g and Na= 118.54mg / 100g), micro minerals (Fe=23.779mg / 100g) were seen in root part. Hence, the study evidence shown that this geranium species can enhance nutrition value and food security as well as natural remedies for the local people